Cyberbullying Policies: a Long Way from Ideas to Practices (KULT_online, 2018)
The monograph Protecting Children Online?: Cyberbullying Policies of Social Media Companies, written by the media scholar Tijana Milosevic, investigates the controversies of the anticyberbullying policies, elaborated and implemented by social media companies (such as Facebook, Twitter, YouTube, Ask.fm etc.). Milosevic inspects the public debates around highprofile cyberbullying accidents and subsequent legal regulations. She focuses on the companies’ corporate documentation addressing this issue and shares the results of her interviews with social media e-safety experts and NGO representatives. This book puts cyberbullying in a broader context of the various contradictions, such as censorship and freedom of speech, state control and industry self-regulation, e-safety and data privacy. Based on her analysis, Tijana Milosevic concludes that it would be extremely challenging to study and prevent cyberbullying without a clear understanding of its context. The book’s detailed focus on legal regulations could be found rather excessive; however spotlighting the crucial differences between the ‘ideal’ corporate principles and its practical implementations surely deserves the attention of media and cultural scholars.